Gender in Technology, Engineering and Design: factors which influence low STEM subject uptake among females at third level - Kiernan, Louise; Walsh, Marie; White, Eoin (International journal of technology and design education, 2023)
Based on social cognitive career theory (SCCT) this study explored the barriers to females choosing STEM disciplines at post-primary level. The study firstly explored national data from all secondary schools in Ireland, to compare subject uptake at the leaving certificate cycle and discipline uptake at third level. Secondly, a focus group was conducted with students in first, third and sixth year at one of Ireland’s top ranked post primary all-female schools to gain insights into subject availability, influencing factors and decision making for subject and discipline choices. The findings show that, some of the factors from the SCCT model have greater influence on the decision making of females to pursue a STEM related discipline at third level. Examining gender disparity under one theme labelled STEM may be skewing the reality of STEM subject uptake among genders. Nationally, females are strongly represented in the science disciplines, out representing males in science and health. Females are significantly underrepresented in technology, engineering, and technology-related design fields. Many aren’t exposed to, encouraged, or informed about these subjects in secondary school. Students’ career choices are mainly influenced by STEM subject availability at second level, career guidance, access to work placements and experience, along with social persuasion from, family, friends, and role models. Some of these sources of persuasion and influence were found to be at risk from bias and perceptions around status. The combination of these barriers in turn contributed to low self-efficacy, negative perceptions, and low interest amongst some females towards some STEM subjects.